Inklusi Sosial Penghayat Kepercayaan; Upaya Mendorong Hak Warga Negara Penganut Kepercayaan Sedulur Sikep Kudus - Ubbadul Adzkiya; Iman Fadhilah (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2020)
Indonesia has a diversity of religions and cultures, so far many people are still discriminated against because they are different from the state's recognized religion. In Kudus Regency, the Sedulur Sikep community as adherents of Adam's religion could not register their marriage, thus facing population administration problems. This service-based research explains how to strive for them to gain access to public services, social acceptance, and policy changes so that they are not discriminated against again. By connecting perspectives on civil and political rights as well as economic, social and cultural. The results show that the root of the problem which afflicts the victim can be spelled out in this column, namely the administrative system of population causes humiliation on the basis of the belief in participation that impacts on exclusion and other exclusions. To overcome this problem, efforts and strategies that are commonly made are changes at the internal level, empowerment, recognition and acceptance.